Analisis Harga (Rokok Eletronik) Terhadap Minat Pembelian di Kalangan Remaja - Ferdi Rizki Syahriar; Febri Ferdian; Syamsul Hidayat (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
In this article, we conduct a price analysis (of electronic cigarettes) on purchasing intentions among teenagers. Based on the data we collected, we found that the price of e-cigarettes influences purchasing intentions among teenagers. Here are some results from our analysis: The price of e-cigarettes is a factor that influences purchase intention among teenagers. If the price of e-cigarettes is too high, then interest in purchasing will decrease. The quality of electronic cigarettes is also a factor that influences purchase intention. If the quality of e-cigarettes does not meet teenagers' needs, their interest in purchasing will decrease. From our analysis, we conclude that to increase interest in purchasing e-cigarettes among teenagers, companies should consider the factors we have identified. By paying attention to price, quality, market and marketing, companies can obtain higher purchasing interest from teenagers